The effect of metronidazole on Bacteroides fragilis and Escherichia coli - Dachs, Gabriele Ursula (Department of Molecular and Cell Biology, 2016)
The antibiotic metronidazole is used extensively in the clinical treatment of anaerobic infections, including those caused by the anaerobic pathogen Bacteroides fragilis. Metronidazole is an inert substance that requires reductive activation to become cytotoxic. In its activated form metronidazole induces DNA damage. Relatively little is known about the cytotoxic effects of this drug in vivo. The aim of the work reported in this thesis was to analyze the mode of action of metronidazole in living systems. Furthermore, the potential for bacterial cells to develop resistance mechanisms to metronidazole is largely unknown, and therefore the role played by B. fragilis genes in influencing the potency of metronidazole was investigated. Bibliography: pages 172-201.